Sir! I'd Rather Go to School, Sir! - Mahdi Majbouri (Institute of Labor Economics (IZA), 2017)
Military service is a popular method of army recruitment for governments of developing countries that are particularly prone to conflict. This study contributes to the largely under-researched issues of military service by looking at an unintended consequence of a military service exemption policy and answering a principal question: is there a fear of conscription among the youth? It uses a discontinuity in the military service law in an under-researched country, Iran, and offers causal evidence that fear of conscription entices young men to get more education against their will. This exogenous increase is used to estimate returns to education.
Keywords: I23; J47; I26; N35; 330; regression discontinuity; natural experiment; coercive labor market; conscription; higher-educational attainment